The Problem of Self-Education in the XX Century: Historical Aspect - Tiholoz, Valentina (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Outstanding pedagogues of the XX century A. Makarenko, S. Rusova, G. Vashchenko, V. Sukhomlinsky promoted theoretical and practical concepts of self-education: objectives, principles, methods and forms of self-education; methodology of self- education, centered on self study using a book as the main source of knowledge; formulation of prospects in self-education; self-education as a means of socialization. In the 20’s – early 30’s A. Makarenko puts into practice the idea of the social character of self-education. Education is impossible when the school and the book are ignored. Therefore the possibility of wide self-education as a kind of prospects opens the way for further development of the whole group. Only self-education of each collective members, living in commune, «only the school and the book can determine our progress». By G. Vashchenko, the child should be encouraged to self-education in the educational process. Key factors of child’s spiritual development, which contribute to their socialization, are self-improvement, self-upbringing and self-education, which reflect their inner world. In the 60’s of XX century V. Sukhomlinsky supplemented the theory and practice of self-education by actual provisions: self-education is a necessary condition for intellectually and spiritually full life; the student’s mental abilities formation is impossible without self-education; the basis of self-education is interest, hobbies, needs for regular updating of knowledge – from the work in hobby groups to the interest in reading books, from books to the specific area of scientific knowledge, from knowledge to creative work.